Temperature-dependent Response to Indoleacetic Acid Is Altered by NH(4)(+) in Cultured Cotton Ovules - Beasley, C. A. (1977)
Unfertilized cotton ovules, cultured in vitro, produced fiber in response to indoleacetic acid (IAA) and/or gibberellic acid (GA(3)). Of the two hormones, IAA produced the greater amount of fiber per ovule, and the effect of both hormones applied simultaneously was approximately additive. Depending upon in vitro culture temperature, a variable number of unfertilized cotton ovules produced fiber in response to 5 μm IAA. The response to IAA was “all or none” for each ovule. The percentage of ovules responding to 5 μm IAA ranged from zero at 28 C to 100 at 34 C. The ability to respond at nonpermissive culture temperatures (i.e. 28 to 30 C) was markedly increased by including 2.5 mm NH(4)NO(3) in the KNO(3)-based medium or by increasing concentrations of IAA. The inclusion of NH(4)(+) in the basal culture medium provided only an increased percentage of ovules producing fiber in the presence of IAA, but did not increase fiber production per ovule. Temperature, like GA(3), increased both the number of ovules producing fiber in response to IAA and the amount of fiber produced per ovule.